2013
DOI: 10.1016/j.jaci.2013.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate receptor 2 protects against anaphylactic shock through suppression of endothelial nitric oxide synthase in mice

Abstract: Background: Sphingosine-1-phosphate receptor-2, S1P 2 , is expressed in vascular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 44 publications
0
45
1
Order By: Relevance
“…When compared with control cells, cells treated with gremlin were characterized by an increased number of intercellular gaps and by the delocalization of vascular endothelial-cadherin and ZO-1 from the cell junctions to the cytoplasm ( Figure 3B). Similar to that described for VEGF-A 165 , 35 the nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester (L-NAME) prevented EC junction disruption in gremlin-stimulated cells ( Figure IV in the online-only Data Supplement). In agreement with these observations, both recombinant gremlin and VEGF-A 165 similarly affected blood vessel permeability in vivo when tested subcutaneously (s.c.) in the Miles assay 36 ( Figure 3C and Cʹ).…”
Section: Creb Mediates the Early Phases Of The Angiogenic Response Ofmentioning
confidence: 52%
“…When compared with control cells, cells treated with gremlin were characterized by an increased number of intercellular gaps and by the delocalization of vascular endothelial-cadherin and ZO-1 from the cell junctions to the cytoplasm ( Figure 3B). Similar to that described for VEGF-A 165 , 35 the nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester (L-NAME) prevented EC junction disruption in gremlin-stimulated cells ( Figure IV in the online-only Data Supplement). In agreement with these observations, both recombinant gremlin and VEGF-A 165 similarly affected blood vessel permeability in vivo when tested subcutaneously (s.c.) in the Miles assay 36 ( Figure 3C and Cʹ).…”
Section: Creb Mediates the Early Phases Of The Angiogenic Response Ofmentioning
confidence: 52%
“…HUVECs between passages 4 and 6 were used for all experiments. MLECs and mouse aortic smooth muscle (MASM) cells were isolated from Pik3c2a flox/flox mice and used for in vitro assays as described previously (8,32,33). HEK293T cells, MASM cells, and Caco2 cells were cultured in 10% FBS (Invitrogen Gibco)-supplemented DMEM for HEK293T and Caco2 cells (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…The balance of S1P 1 and S1P 2 receptors in the endothelium may determine the regulation of vascular permeability by S1P (Sanchez et al 2007). More recently, Zhang et al also reported that inhibition of S1P 2 signaling dramatically decreased PLS-induced vascular permeability (Zhang et al 2013; Cui et al 2013). However, a recent study showed that S1P 2 protects mice from vascular barrier disruption elicited by either antigen challenge or PAF injection and that this protective effect of S1P 2 is mediated through suppression of anaphylaxis-associated endothelial nitric oxide synthase (eNOS) stimulation (Cui et al 2013).…”
Section: Sphingosine 1-phosphate Regulates Vascular Leak In Diseasementioning
confidence: 96%
“…More recently, Zhang et al also reported that inhibition of S1P 2 signaling dramatically decreased PLS-induced vascular permeability (Zhang et al 2013; Cui et al 2013). However, a recent study showed that S1P 2 protects mice from vascular barrier disruption elicited by either antigen challenge or PAF injection and that this protective effect of S1P 2 is mediated through suppression of anaphylaxis-associated endothelial nitric oxide synthase (eNOS) stimulation (Cui et al 2013). Thus the in vivo role of S1P 2 in inflammatory conditions such as sepsis and anaphylaxis is not yet fully understood.…”
Section: Sphingosine 1-phosphate Regulates Vascular Leak In Diseasementioning
confidence: 96%
See 1 more Smart Citation